Dr. Kenneth Rothaus — Deep Plane Facelift — New York - Rothaus, Kenneth (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kenneth Rothaus, practicing in New York, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003195; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; new york